iTRAQ-based proteomic profiling of salt-tolerant and salt-sensitive potato (Solanum tuberosum) cultivars under salinity stress - Zhang, Zhaojuan; Wang, Yongsheng; Zhao, Shuai; Chen, Fangyu; Huang, Rongyu; Na, Tiancang; Guo, Yuchun (Frontiers in Plant Science, 2025)
IntroductionSoil salinity represents a significant abiotic stress factor that adversely affects potato yield and quality. Elucidating the molecular mechanisms underlying salt tolerance is crucial for the development of resilient cultivars. This study examines the proteomic responses of salt-tolerant (M5008) and salt-sensitive (D516) potato cultivars under saline conditions.MethodsA quantitative iTRAQ-based proteomic approach was utilized to analyze protein expression profiles in the roots of both cultivars exposed to 150 mM NaCl stress. Bioinformatics analyses—including Gene Ontology (GO) annotation, Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment, and protein–protein interaction (PPI) network construction—were performed. Key results were further validated by quantitative real-time PCR (qRT-PCR).ResultsA total of 511 and 456 differentially accumulated proteins (DAPs) were identified in D516 and M5008, respectively. These DAPs were predominantly involved in redox homeostasis, sugar and osmotic metabolism, and phytohormone signaling pathways. PPI network analysis revealed six major functional modules, including glucose metabolism, translational initiation, and ubiquitin-mediated protein catabolism. The expression patterns of key proteins (G6PD1, P5CSA, PP2A2, TPS1, GAPCP1, HEXO1) were consistent with their corresponding mRNA levels, supporting their functional roles in the salt stress response.DiscussionThe salt-tolerant cultivar M5008 demonstrates a coordinated and multifaceted response to salinity stress, characterized by enhanced antioxidant defense, efficient energy utilization, and precise regulation of protein synthesis and degradation. In contrast, the salt-sensitive cultivar D516 exhibits a disorganized and less effective response. These findings offer new insights into the proteomic mechanisms governing salt tolerance in potato and identify potential candidate genes for use in future breeding and genetic engineering efforts.